Hungarian Monitoring, 6 May 1988 . [Magyar rádiófigyelő], 1988. május 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Polish strike situation - French presidential elections - Socialist journalists in Panama Domestic Affairs: - Károly Grósz holds press conference in London - Hungary-Mozambique foreign ministers' talks - Hungary's relationship with Interpol - Mihály Kökény's experience of the WHO conference in Geneva - Wage reform and economic development - Language teaching in foreign language high schools Economy: - Drafting the new companies law - Interview with managing director of Merkur on this year's car imports Külpolitika: - Lengyelországi sztrájk-helyzetkép - Francia elnökválasztások - Szocialista újságírók Panamában Belpolitika: - Grósz Károly sajtótájékoztatót tart Londonban - Magyar-mozambiki külügyminiszteri tárgyalások - Magyarország és az Interpol kapcsolata - Kökény Mihály tapasztalatai az Egészségügyi Világszervezet genfi kongresszusáról - Bérreform és gazdasági kibontakozás - Nyelvtanítás az idegen nyelvű gimnáziumokban Gazdaság: - Az új társasági törvény tervezete - Interjú a Merkur vezérigazgatójával az idei autóimportról